Measurement and Analysis in Transforming Healthcare Delivery Volume 2: Practical Applications to Engage and Align Providers and Consumers - Sax, Harry C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume is complementary to Volume 1: Quantitative Approaches in Health Systems Engineering which provides in-depth analysis of the statistical and quantitative aspects of Health Systems Engineering. Volume 2: Practical Applications to Engage and Align Providers and Consumers builds upon these concepts with the integration of additional economic, performance and quality measures. Stressing the importance of changes in the economics of health care financing, it will serve as a resource for not only leaders of organizations, but also providers who will be practicing a different type of medicine from that of which they were trained. After defining the challenges, the authors will quantify and define funds flows and various margins necessary for viability, how providers will be measured and rewarded for quality, and the importance of accurate dashboard of physician performance. Types of payment systems, including capitation, ACOs, risk contracts, and hybrid forms of fee for service will be defined and their relative advantages discussed. Lessons from other countries that provide high quality care at a lower cost will be examined for applicability to our challenges. Finally, experts in leadership will focus on influencing behavior to achieve results while remembering that healthcare is about the patient. This textbook will serve as a useful resource for clinicians, healthcare executives, governmental agencies, and emerging leaders in organizations.
Healthcare Transformation-What are the Challenges? -- Terminology and Applications: Hospital Performance Measures -- Measurements and Analysis in Transforming Healthcare Deliver-Terminology and Applications: Physician Performance -- Assuring Appropriate Care -- Aligning Medical Staff within the Academic Medical Center -- Aligning Healthcare Systems -- Influencing with Integrity -- Perspectives from Single Payer Systems -- Leadership to Encourage and Sustain Performance.
Keywords: Medicine; Health administration; Medicine & Public Health; Health administration